PENGARUH ASPEK KEUANGAN DAN MODAL MANUSIA TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH (UMKM) (Studi Kasus: UMKM di Wilayah Kota Pekanbaru) - Syahsudarmi, Siti (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The purpose of this study is to determine and analyze the capacity of financial aspect and human capital of financial performance of SMEs in Pekanbaru City. This research use descriptive analysis method and verification with technical analysis of Partial Least Square (PLS) with primary data from questionnaire to 20 UMKM as respondent. Data are classified into three characteristics, ie micro, small and medium enterprises grouped based on business turnover per year. Then measured factor loading (convergent validity), discriminant validity, reliability, coefficient of determination, and path coefficient by using SmartPLS. The results showed that the financial and human capital have a significant influence on financial performance, and human capital has a significant influence on the financial aspects